INCREASING MATHEMATICS LEARNING OUTCOMES THROUGH COOPERATIVE MODEL TYPE TEAMS GAMES TOURNAMENT ASSISTED WITH BINGO MEDIA - Bintang Fahlia Lestari; Andika Adinanda Siswoyo; Elvina Octavia; Wijining Tri Wulan Suci; Ineke Putri Wicandara (Citra Dharma Cindekia, 2022)
One way to improve students understanding of mathematics is to present mathematics learning in the form of games. The purpose of this study was to determine the increase in mathematics learning outcomes for third grade students at SDN Kedung Peluk 1 due to the application of the TGT type cooperative learning model with bingo media. The data in the study were collected using observation, interview, documentation and test techniques. The research was conducted in 2 cycles with reflection in each cycle. Based on the analysis of the data obtained, the third grade students of SDN Kedung Peluk 1 experienced an increase from cycle 1 to cycle 2. In cycle 1 students obtained an average score of 68, while in cycle 2 obtained an average score of 90. When carrying out learning observations carried out by observer, which proves that the team games tournament (TGT) cooperative learning model is very well applied in learning, so that students experience an increase in learning outcomes and are expected to be used as references for the next teaching and learning process. Thus, it can be concluded that the team games tournament (TGT) cooperative learning model assisted by bingo media is effectively applied during the teaching and learning process.